MICROBIOLOGICAL EVALUATION OF ANTIMICROBIAL ACTION OF DISINFECTANT AND ANTISEPTIC AGAINST STRAINS STAPHYLOCOCCUS AUREUS, ISOLATED FROM BACILLICARRIERS - Кочнєва, О.В.; Коцар, О.В.; Петренко, Л.О.; А. А. П’ятигор (World of Medicine and Biology, 2016)
A special role among the causative agents of nosocomial infections are strains of Staphylococcus aureus. Bacillicarriers among medical staff are a constant reservoir of infection in hospitals. The mucous membranes of the nose and throat medical professionals are often colonized by microorganisms, which are poly-resistance to chemotherapeutic agents. The main measures of prevention of hospital infections is the use of antiseptics and disinfectants. To date, the number of resistant strains to these facilities increases. Analysis of the research results revealed that out of 248 surveyed medical students allocated 19,4 % of strains of S. aureus, among which are found 6,4 % of MRSA strains. In determining the sensitivity of strains of S. aureus to disinfectants and antiseptics disk diffusion method is shown that a higher antimicrobial activity possessed lizofarmin solution 1%– 82,4±4,9 % of sensitive strains. The most active substance were benzoyl peroxide – 84,3±2,3%, and neosteril – 72,1±3,6 % of sensitive strains. MRSA strains were resistant to almost all antiseptics and disinfectants, with the exception of 1% solution lizofarmin – 18,2±4,2 % and benzoyl peroxide – 16,5±5,1 % of sensitive strains. So, the сhoice of effective antiseptics and disinfectants have to according high antimicrobial sensivity strains of S. aureus, especially given the presence of methicillin-resistant.
Keywords: Staphylococcus aureus; resistance; disinfectants; antiseptics